Adoption of SaaS-based ERP by SMEs in an emerging market economy : giving up control over mission critical business software - De Wet, Philippus Bernardus (Stellenbosch : Stellenbosch University, 2018)
Thesis (MA)--Stellenbosch University, 2018.